FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUME EKSPOR KAYU MANIS INDONESIA - Fauziah Arda Humaira; Dini Rochdiani (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Cinnamon is one of indonesia's plantation export commodities that is quite potential and has expectations for the country's foreign exchange receipts. Cinnamon is not Indonesia's main export commodity, but cinnamon is indonesia's main plantation commodity and has great potential to be exported. There are conditions that are not in line between the production volume and the export volume of Indonesian cinnamon where the production volume shows a downward trend, while the export volume shows an increasing trend. This study aims to analyze what factors influence the export volume of Indonesian cinnamon and find out what factors have the most dominant influence on the export volume of Indonesian cinnamon. This research uses quantitative research design with literature study method. Data in this study in the form of time series data includes annual data during the period 1989 - 2018 (30 years). Data analysis techniques used are classical assumption test analysis, multiple linear regression analysis, and statistical test analysis. The results showed that the variable export price of cinnamon, the real exchange rate of rupiah against usd, indonesia's real GDP, and the area of Indonesian cinnamon land had a significant effect on the export volume of Indonesian cinnamon, while the variable amount of cinnamon production and the real GDP of the USA had an insignificant effect on the export volume of Indonesian cinnamon. The most dominant factor affecting the export volume of Indonesian cinnamon is the export price of cinnamon.